O pensamento humanista de Paulo Freire na Pedagogia do Oprimido - Buda, Ana Maria da Silva (2022)
This dissertation aims to disseminate the humanist thought of Paulo Freire expressed in his main work, Pedagogy of the Oppressed. It uses the methodology of literature review through publications by Freire himself (1989, 1992, 2014, 2020), Gadotti (1996), Saviani (2019), Ana Maria Araújo Freire (2017), Beisiegel (2010) and Cortella (2017) and consultations of online collections, which preserve the memory of the patron of national education, such as the Paulo Freire Institute, the Paulo Freire Chair, and others. The first chapter brings the humanization in Freire, constituted in his training as an educator, and the contributions to Brazilian education, Latin America and the world, based on his biography. The theoretical analysis of the work Pedagogia do Opprimido investigated in the second chapter makes references to the timelessness and predicts the viability of the new, with the effort of all of us. The third chapter presents the entire Freirean trajectory as he applied his theory of dialogic action at the head of the Municipal Department of Education, to conclude that the unknown viable is possible, with a lot of effort, and to hope is a verb that is to be conjugated by all of us who believe in education, since the concept of humanism, object of this investigation, is a fundamental element of Freire's pedagogy.